AUTOMATED TASK MANAGEMENT SYSTEM USING ANALYTICAL HIERARCHY PROCESS - Sonya Meitarice; Mumtaz Begum Peer Mustafa; Dedek Okta Andi (JURNAL TEKNIK INFORMATIKA, 2020)
In today’s competitive environment, students have to manage a great variety of tasks, and sometimes, due to poor time management, they fall behind in completing the tasks well and on time. Thus, this research presents the research and development of an automated task management system using Analytical Hierarchy Process (AHP) measurement for task monitoring and provides alerts for university students, which can continuously monitor the student’s task performance. To achieve the objective of this research, the following methodology was adopted. First, the research identifies suitable measures of poor time management, best time management practices for university students, and suitable solution for developing the proposed system. A preliminary investigation was carried out to identify problem faced by students with their task management and the impact on their academic performance. The respondents of this preliminary investigation are undergraduate and postgraduate students from the Faculty of Computer Science and Information Technology at the University of Malaya that have responded to a survey questionnaire. Based on the outcome of the preliminary investigation, it is clear that students prefer a computer application to constantly monitor tasks over the internet will ease the tasks of users.